APLIKASI PENGECEKAN KONDISI KESIAPAN INSTRUMENT DAN EQUIPMENT - Abdul Malik; Siti Sufaidah; Moch. Anshori Aris Widya (KH. A. Wahab Hasbullah University, 2018)
In management motor and electro in PT. Semen Gresik Tbk for check condition of instrument and equipment use manual program. For detect condition it user collect many data, that make checking proses not efficient. Now Application program for check condition equipment and instrument make user require data recur that make very much data entry. For check condition of instrument and equipment user have to complete the instrument code. After this application went execute and search the data in database of application. After the data is finds application will show the data in form in automatic on a scale. Continued, the data is process with application for detect condition of equipment and instrument in ready, no, or the status is warning. Product from this examination is application program for check condition of instrument and equipment to PT. Semen Gresik Tbk this program give information from condition of instrument and equipment every time and this report in graph. Keyword: Application program, Checking condition, Equipment, Instrument, Graph